2012
DOI: 10.1111/j.1476-5381.2011.01648.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of a small‐molecule agonist for the chemokine receptor CXCR3

Abstract: BACKGROUND AND PURPOSEThe chemokine receptor CXCR3 is a GPCR found predominantly on activated T cells. CXCR3 is activated by three endogenous peptides; CXCL9, CXCL10 and CXCL11. Recently, a small-molecule agonist, VUF10661, has been reported in the literature and synthesized in our laboratory. The aim of the present study was to provide a detailed pharmacological characterization of VUF10661 by comparing its effects with those of CXCL11. EXPERIMENTAL APPROACHAgonistic properties of VUF10661 were assessed in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 57 publications
(87 reference statements)
8
78
0
Order By: Relevance
“…The day after transfection, cells were trypsinized, resuspended into fresh culture medium, and plated in poly(L-lysine)-coated 48-well assay plates. The enzyme-linked immunosorbent assay (ELISA) procedure was performed as reported earlier (Scholten et al, 2012b). Briefly, 48 hours after transfection, the cells were fixed with 4% formaldehyde solution, permeabilized by 0.5% Nonidet P40, and stained with anti-CXCR3 antibody mAb160 (R&D Systems, Minneapolis, MN), and subsequently with goat anti-mouse horseradish peroxidaseconjugated antibody (BioRad Laboratories, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The day after transfection, cells were trypsinized, resuspended into fresh culture medium, and plated in poly(L-lysine)-coated 48-well assay plates. The enzyme-linked immunosorbent assay (ELISA) procedure was performed as reported earlier (Scholten et al, 2012b). Briefly, 48 hours after transfection, the cells were fixed with 4% formaldehyde solution, permeabilized by 0.5% Nonidet P40, and stained with anti-CXCR3 antibody mAb160 (R&D Systems, Minneapolis, MN), and subsequently with goat anti-mouse horseradish peroxidaseconjugated antibody (BioRad Laboratories, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
“…CCX-CKR cDNA was fused in-frame with Renilla luciferase (Rluc) using a PCR-based method, as previously described (22). ␤-Arrestin1 and ␤-arrestin2 enhanced yellow fluorescent protein EYFP fusion constructs were described previously (23). The R3.50A mutant of CCX-CKR was constructed by site-directed mutagenesis and re-introduced into pcDEF3 (CCX/R3.50A).…”
Section: Methodsmentioning
confidence: 99%
“…7D). Binding of cAMP to the EPAC domain of the biosensor results in a decrease of intramolecular BRET (23,24).…”
Section: Ccx-ckr Il2/3 Chimeras Stimulate Campmentioning
confidence: 99%
“…These three compounds display a diversity of affinities as measured using [ 3 H]VUF11211 (from pK i 5 7.7-9.0). Different types of ligands, ranging from inverse agonists to agonists, might recognize different subsets of CXCR3 populations (Cox et al, 2001;Scholten et al, 2012b). For example, agonist binding to GPCRs is often dependent on G-protein precoupling.…”
Section: Characterization Of [mentioning
confidence: 99%
“…Fortunately, understanding of these interactions has started to emerge in the past years (Bernat et al, 2012;Nedjai et al, 2012;Scholten et al, 2012bScholten et al, , 2014. In a recent study (Scholten et al, 2014), we reported on the binding mode of two CXCR3 ligands originating from the 8-azaquinazolinone class (NBI-74330) and the piperazinylpiperidine class (VUF11211, (S)-5-chloro-6-(4-(1-(4-chlorobenzyl) piperidin-4-yl)-3-ethylpiperazin-1-yl)-N-ethylnicotinamide) using site-directed mutagenesis in conjunction with in silico modeling of CXCR3.…”
Section: Introductionmentioning
confidence: 99%